PEMANFAATAN LIMBAH AIR KELAPA MENJADI PRODUK COCO CIDER : KAJIAN PENAMBAHAN GULA DAN WAKTU FERMENTASI - Wrasiati, Luh Putu (Bumi Lestari, 2013)
Abstract The coconut waste water contain some nutrients, micronutriens, and minerals such as vitamin C, biotin, riboflavin, folic acid, amino acid, carbohydrate, calcium, phosphorous and iron. The product of coconut waste water is popularly known as nata-de-coco. Besides that, the coconut waste water can also produced as alcohol beverages like coco cider. This research was conducted in order to observe the effect of sucrose addition and fermentation time on the characteristics of coco cider, and to determine the best characteristics of coco cider. This research is expected to provide the information about the amount of sugar should be added and fermentation time in production of coco cider. The design experiment used in this research was the randomized complete design with two factors, i.e. the ratio of sugar added (5, 10, 15, and 20%) and the fermentation time (2, 4, and 6 days). The variables observed included alcohol content, total sugar content, pH, and sensory evaluation such as taste, aroma, and overall acceptance. The results indicated that the interaction between sucrose addition and fermentation time significantly affected the alcohol content and total sugar content of coco cider, the more the sucrose added and the longer the fermentation time, the higher the alcohol content and the less the total sugar content. The sensory evaluation indicated that the good coco cider was produced from 10 percen of sucrose and fermented in two days with the characteristics: the score of taste, aroma and overall acceptance was between 3 and 4, alcohol content was 5.3, pH was 3.9, and total sugar content was 10.75 percents.
Keywords: Keyword: coconut waste water,coco cider, sucrose addition, and fermentation time